2021
DOI: 10.1016/j.apnr.2021.151476
|View full text |Cite
|
Sign up to set email alerts
|

Resilience as a mediator between compassion fatigue, nurses' work outcomes, and quality of care during the COVID-19 pandemic

Abstract: Background Nurses in the frontline of the battle against COVID-19 are highly vulnerable to compassion fatigue (CF), which may affect their mental health, work effectiveness, and patient safety outcomes. However, no studies have investigated nurses' CF in relation to job outcomes and care quality during the pandemic. Aims This study aims to examine the mediating role of resilience in the relationship between CF and frontline nurses' job outcomes (job satisfaction and tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
111
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 57 publications
9
111
1
4
Order By: Relevance
“…Previous studies of healthcare workers during the COVID-19 pandemic showed psychological resilience has a protective mediating role between depression, perceived stress and personal burnout, and mental health, which may affect the quality of life ( 28 , 29 ). Similarly, front-line nurses during the COVID-19 pandemic experienced a medium to high level of fatigue but their psychological resilience reduced the negative impact of fatigue on their job satisfaction and turnover intention ( 30 ). Nearly half of healthcare providers in HIV clinics report experiencing significant psychological distress, but psychological resilience and institutional support have protective mediating effects between COVID-related stressors and psychological distress, which could disrupt one's quality of life ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of healthcare workers during the COVID-19 pandemic showed psychological resilience has a protective mediating role between depression, perceived stress and personal burnout, and mental health, which may affect the quality of life ( 28 , 29 ). Similarly, front-line nurses during the COVID-19 pandemic experienced a medium to high level of fatigue but their psychological resilience reduced the negative impact of fatigue on their job satisfaction and turnover intention ( 30 ). Nearly half of healthcare providers in HIV clinics report experiencing significant psychological distress, but psychological resilience and institutional support have protective mediating effects between COVID-related stressors and psychological distress, which could disrupt one's quality of life ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly during the COVID-19 crisis, the maintenance of high-quality distance education, the volume of future nursing workforces, and the quality of care across fields worldwide are urgent public health issues ( Labrague and de los Santos, 2021 ). Sputum suction is an important skill in clinical nursing, especially for patients with endotracheal tube placement, tracheostomy, and ventilator use ( Seema et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Literature strongly supports a correlation between resilience, stress, and retention 3 . Overall, highly resilient nurses cope with stress more effectively than nurses with lower levels of resilience 2 . At MDMC, we decided to organize volunteer inpatient clinical nurses who had demonstrated a high level of engagement as validated by their managers to launch a newly formed shared-governance council called the Engagement and Resilience Council.…”
mentioning
confidence: 99%
“…An abundance of literature has focused on ways to improve resiliency, typically consisting of interventions done off-shift 1 . Multimodal resilience building performed away from a nursing unit over time is reported to improve compassion fatigue and burnout, 2 strengthening job satisfaction and retention in nurses.…”
mentioning
confidence: 99%
See 1 more Smart Citation